Stripe : helping money move on the Internet - Markovich, Sarit, (SAGE Knowledge. Cases., 2017)
This case features Stripe, a startup that enables merchants to accept payments from customers on the web, on mobile devices, and at the point of sale (POS). Stripe was launched in 2011 by the Collison brothers and quickly gained traction with e-commerce startups, particularly software and platform developers who needed help building their payment processing infrastructures. Stripe incurred high fixed costs in developing its platform and had low margins per transaction, so the company needed to reach high processing volumes (i.e., scale) to survive. This was challenging, as Stripe competed with large payment processors and traditional banks that had high processing volumes and were able to offer merchants significantly lower rates than Stripe. Still, merchants valued Stripe's solution because it was simple and versatile. Students assume the role of the Collisons to think about possible strategies Stripe could pursue to process higher volumes of transactions. Students are challenged to think about the potential response of the incumbents to Stripe's different growth alternatives. The teaching note presents the Value Net framework and discusses the importance of considering complementors and their effect on a firm's strategy. Finally, a discussion about Stripe's potential entry into the Indian market allows students to apply the concepts they learned in the discussion of a new market.